[OP.5C.10] GENDER DEPENDENCE OF ALDOSTERONE TO RENIN RATIO IN A PEDIATRIC POPULATION. (September 2017) - Morganti, A.; Tassistro, E.; Nava, E.; Orlando, A.; Turolo, L.; Giussani, M.; Manolopoulou, J.; Parati, G.; Antolini, L.; Genovesi, S.
Abstract : Objective: Aldosterone to renin ratio (ARR) is widely used as screening test of primary hyperaldosteronism, but little is known of the reference values of ARR in pediatric age. Aim of this study was to evaluate ARR values and associated factors in a population of Italian children and adolescents. Design and method: In blood samples collected in sitting position in 287 children and adolescents attending a Pediatric Unit of Preventive Medicine (52% males aged 4–18 years), we measured plasma aldosterone and plasma renin concentrations (PAC, ng/dL and PRC mU/L) with the immunochemiluminescent method and calculated the relevant ARR values. Pubertal status, weight, height, heart rate, blood pressure, sodium, potassium, glomerular filtration rate and HOMA index were also assessed. Results: Median PAC was fairly similar throughout the age classes (4–8.9), (9–10.9), (11–12.9), (13–18) in both genders (ranging from 7.5 to 9.9 ng/dL in males and from 11.0 to 12.6 ng/dL in females for the first to the fourth age class). In males median PRC was similar across age classes (ranging from 58.2 to 55.5 mU/L), whereas in females PRC progressively fell from 61.5 to 36.6 mU/L (p < 0.001).Also, PRC was significantly lower in pubertal than in pre-pubertal females (46.1 vs 58.7 mU/L, p = 0.003). No difference was observed between pubertal and pre-pubertal males. Median ARR was similar throughout the age classes in males (from 0.18 to 0.19), whereas it increased significantly from 0.19 to 0.36 in females (p = 0.03). In an adjusted multiple regression analysis PAC and PRC were significantly correlated in both genders (p < 0.0001). In females, age was inversely related with PRC (p = 0.0001) and directly related with ARR (p = 0.01). The corresponding models in males did not show any significant association. Conclusions: In a pediatric population with increasing age ARR values diverge between genders due to the progressive reduction of PRC in females. It appears that age and puberty are the driving factors of this gender effect.